An Effective Modulus Predictive Method of Graphene Epoxy Nanocomposites. (September 2020) - Wei, Huazhen; Wang, Danyong; Zhang, Jianqin; Zhang, Haiyun; Li, Shuhu
Abstract: Interfacial interaction between flaked graphene and resins was the key element of effecting whether graphene as nanofillers could improve some of the properties of pure resin. Based on really materials and applied manufacturing process, a new kind of an effective modulus predictive method for resins modified with graphene which could compute and analyze modulus of any content ratio of graphene in the resin with only one content ratio was built in order to provide theoretical foundations for design and property of resins modified with graphene. According to practically different materials system and corresponding manufacturing processes, few experiments which only needed elastic modulus of resins modified with one random content-ratio graphene were made to predict effective elastic modulus of any other content ratio of graphene modifying resins under the same manufacturing processes by obtaining experimental constants based on numerical progressive iterative approximation method and compute the above experimental constants as basic materials parameters so as to build the whole analysis model in the next step. An excellent agreement was found between data obtained from this study and the experiment.